Effect of acrylic polymers on physical parameters of spheronized pellets using an aqueous coating system - Akhter, Afsana; Kibria, Golam (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this study was to develop ambroxol hydrochloride sustained release pellets by an extrusion-spheronization echnique and subsequent coating with acrylic polymers. Acrylic polymers like Eudragit RL 30 D, Eudragit RS 30 D and Eudragit NE 30 D were used as release retarding coating polymers. The release retarding capability of these polymers was also investigated. In each case, 10% polymer on dry basis was loaded. The flow property, surface roughness as well as the drug release behavior of the pellets was found to be the subject of types of polymers. About 35% drug was released at the first hour in 0.1N HCl media (pH 1.2) from Eudragit RL 30 D-coated pellets but from Eudragit RS 30 D and Eudragit NE 30 D-coated pellets, only 13.75 and 2.43% drug was released, respectively. In buffer media (pH 6.8), about 54% drug was released at the first hour from Eudragit RL 30 D-coated pellets but only 64% drug was released at 10 h. From Eudragit RL 30 D- and Eudragit NE 30 D-coated pellets only 7.28 and 1.14% drug was released at 1 h, respectively, but about 5.14 and 5.86 h was required for 50% drug release from these two polymers and about 80% drug was released at 10 h.The functional groups present in the polymeric films played a significant role on in vitro release kinetics of the drug from the coated pellets. Different kinetic models like zero order, first order and Higuchi were used for fitting the drug release pattern. The Higuchi model was the best fitted for ambroxol release from the coated pellets. The drug release mechanism was derived with Korsmeyer equation.